Improving patient access to specialized health care: the Telehealth Network of Minas Gerais, Brazil - Maria Beatriz Alkmim; Renato Minelli Figueira; Milena Soriano Marcolino; Clareci Silva Cardoso; Monica Pena de Abreu; Lemuel Rodrigues Cunha; Daniel Ferreira da Cunha; Andre Pires Antunes; Adélson Geraldo de A Resende; Elmiro Santos Resende; Antonio Luiz Pinho Ribeiro (The World Health Organization, 2012)
PROBLEM: The Brazilian population lacks equitable access to specialized health care and diagnostic tests, especially in remote municipalities, where health professionals often feel isolated and staff turnover is high. Telehealth has the potential to improve patients' access to specialized health care, but little is known about it in terms of cost-effectiveness, access to services or user satisfaction. APPROACH: In 2005, the State Government of Minas Gerais, Brazil, funded the establishment of the Telehealth Network, intended to connect university hospitals with the state's remote municipal health departments; support professionals in providing tele-assistance; and perform tele-electrocardiography and teleconsultations. The network uses low-cost equipment and has employed various strategies to overcome the barriers to telehealth use. LOCAL SETTING: The Telehealth Network connects specialists in state university hospitals with primary health-care professionals in 608 municipalities of the large state of Minas Gerais, many of them in remote areas. RELEVANT CHANGES: From June 2006 to October 2011, 782 773 electrocardiograms and 30 883 teleconsultations were performed through the network, and 6000 health professionals were trained in its use. Most of these professionals (97%) were satisfied with the system, which was cost-effective, economically viable and averted 81% of potential case referrals to distant centres. LESSONS LEARNT: To succeed, a telehealth service must be part of a collaborative network, meet the real needs of local health professionals, use simple technology and have at least some face-to-face components. If applied to health problems for which care is in high demand, this type of service can be economically viable and can help to improve patient access to specialized health care.